Cytotoxic Potential of Combination of Hibiscus sabdariffa L. Extract and Cisplatin against HeLa Cervical Cancer Cell Line: A Study of Antiproliferative Activity and Apoptosis Induction - Nurani, Laela Hayu; Azzahra, Fara; Utami, Dwi; Edityaningrum, Citra Ariani; Guntarti, Any; Irham, Lalu Muhammad; Daud, Intan; Khairurrizki, Amanda; Putra, Ichsan Luqmana Indra; Ismiyati, Nur; Rofida, Siti; Sugiyanto, Sugiyanto (Majalah Obat Tradisional, 2025)
Cervical cancer is one of the most prevalent cancer types, making the development of effective anticancer agents critical. Cisplatin (CIS) is a drug that has been used to treat cancer, but it also affects normal cells. Hibiscus sabdariffa L. extract (HSE), which has the potential as an anticancer agent, can be developed as a co-chemotherapy with CIS. This study aimed to determine the potential of HSE as a co-chemotherapy with CIS against HeLa cervical cancer cells and determine specific and non-specific parameters of the studied extract. Hibiscus sabdariffa L. (HS) simplicia powder was macerated with 96% ethanol. An in vitro evaluation was carried out on antiproliferative activity by calculating the doubling time. Additionally, a selectivity test was conducted to calculate combination index (CI) values based on the microtetrazolium (MTT) method. Apoptosis mechanisms were explored based on immunocytochemical methods using p53, caspase, and Bax antibodies, followed by an observation of apoptotic induction using a flow cytometer. The HSE and CIS selectivity index values obtained for Vero cells and HeLa cells were 209 and 278, respectively. The antiproliferation test results showed that the combination of HSE and CIS could better extend the doubling time of cells compared to the negative control. This combination also demonstrated a strong synergistic effect, with a CI value of 0.001. The extract as a co-chemotherapy with CIS was capable of increasing the expression of p53, caspase-3, and Bax. The flow cytometry analysis results indicated that HSE could induce apoptosis. Based on the results on the IC50 and CI value of HSE, as well as on the doubling time and apoptosis induction of HSE-influenced HeLa cells, it is concluded that HSE has the potential as a co-chemotherapy against cervical cancer.